Novel methodology for the calculation of the enthalpy of enclathration of methane hydrates using molecular dynamics simulations. (1st June 2020) - Tsimpanogiannis, Ioannis N.; Michalis, Vasileios K.; Economou, Ioannis G.
Abstract : Methane hydrates are encountered in a plethora of industrial and geological or environmental applications. In the current study, we present a novel methodology which is based on molecular dynamics simulations for the calculation of the enthalpy of enclathration of sI methane hydrates. Simulations are performed along the three-phase (Hydrate – Liquid water – Vapour; H–Lw –V) equilibrium line in the temperature range 274–310 K. The methodology takes into account the two different types of cages that are present in the sI methane hydrate and provides results for the enthalpy of enclathration for both types of cages, while it avoids performing calculations with the metastable, completely empty hydrate lattice. The formulation proposed is general and can be also applied to sII hydrates, while it can be modified/extended appropriately for use in the case of sH hydrates. Comparison is provided with available data from the literature and good agreement is observed. GRAPHICAL ABSTRACT: UF0001